2016
DOI: 10.1002/2015wr018105
|View full text |Cite
|
Sign up to set email alerts
|

Systems modeling to improve the hydro‐ecological performance of diked wetlands

Abstract: Water scarcity and invasive vegetation threaten arid‐region wetlands and wetland managers seek ways to enhance wetland ecosystem services with limited water, labor, and financial resources. While prior systems modeling efforts have focused on water management to improve flow‐based ecosystem and habitat objectives, here we consider water allocation and invasive vegetation management that jointly target the concurrent hydrologic and vegetation habitat needs of priority wetland bird species. We formulate a compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This shows that the optimized model can effectively increase the restored habitat area of rare water birds. Alminagorta et al [40] confirmed this by using the optimization model to increase the habitat area of water birds by the optimization scheme to twice that of the basic scheme. On the other hand, on comparing the interval value of the restored habitat area by the three optimization schemes, it can be found that the upper bound value improved significantly as compared to the lower bound value, which is also highlighted from a comparison of Figure 4b,c.…”
Section: Intakesmentioning
confidence: 91%
See 1 more Smart Citation
“…This shows that the optimized model can effectively increase the restored habitat area of rare water birds. Alminagorta et al [40] confirmed this by using the optimization model to increase the habitat area of water birds by the optimization scheme to twice that of the basic scheme. On the other hand, on comparing the interval value of the restored habitat area by the three optimization schemes, it can be found that the upper bound value improved significantly as compared to the lower bound value, which is also highlighted from a comparison of Figure 4b,c.…”
Section: Intakesmentioning
confidence: 91%
“…Under such circumstances, preparing a reasonable and scientific ecological water replenishment scheme for the MNNR taking all of these factors into consideration becomes an important question. The system optimization model can connect the system components such as hydrology, ecology, and management, allowing managers to evaluate options for allocating scarce resources to optimize management objectives [40]. Due to its complexity, a water resource management system inevitably has some uncertain factors, including water supply and demand, flood resources, and economic parameters, and so on [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…The spatial expression can use quantitative data such as the spatial distribution of wetlands, the distribution of wetlands, and the geographical weight matrix of wetlands. The analysis unit can use geographic grid, geomorphological unit [ 11 ], land unit, wetland unit, and other methods, and the analysis method can adopt the form of spatial correlation matrix. The relationship between land types and ecosystem service types and their ability to provide corresponding services are represented by a supply matrix.…”
Section: Wetland Ecosystemmentioning
confidence: 99%
“…Operational and stochastic variables are commonly encountered jointly in a variety of water‐related setting, for example, eutrophication of shallow water systems (Pastres et al., 1999), hydrological and financial management of river systems (Hamilton et al., 2022), protection of diked wetlands (Alminagorta et al., 2016), water management within the socio‐hydrological perspective (Elshafei et al., 2016), management of sewer overflows in a urban river (Riechel et al., 2016), risk assessment of drinking water supply (Cantoni et al., 2021), urban flood scenarios (Wu et al., 2021), live cycle of small water resource recovery facilities (Thompson et al., 2022) and tomato production in urban environments (Peña et al., 2022), regulation of rivers under climate change (Patil et al., 2022), management of grape harvest (Lo Piano et al., 2022), impact of coastal shrimp ponds in saltwater intrusion (Hou et al., 2022), crop yields under climate change (Karimi et al., 2022), analysis of water networks (Chen et al., 2022), investigation of riparian freshwater lenses (Jazayeri et al., 2021), impact of partially penetrating barriers on island freshwater lenses (Yan et al., 2021), impact of water withdrawals on waterfalls features (Schalko & Boes, 2021), functioning of sewer networks (Dobson et al., 2022), sediment management for dams (Niu & Shah, 2021), wave propagation in pressurized pipe (Wang, 2021) and algal growth dynamics (Hariz et al., 2023), just to name a few.…”
Section: Introductionmentioning
confidence: 99%